Impact of extended and restricted antibiotic de-escalation on mortality - Lin, Teh Hwei (2020)
More data is needed about the safety of antibiotic de-escalation in specific clinical situations as a strategy to reduce exposure to broad-spectrum antibiotics. To compare the survival probabilities of patient de-escalated (early or late) against those not de-escalated on extended or restricted antibiotic, to determine the association of patient related , clinical related , and pressure sore/device related characteristics on all-cause 30-day mortality and determine the impact of early and late de-escalation antibiotic de-escalation on 30-day all-cause mortality. This retrospective cohort study was conducted by reviewing medical records of patients eligible for antibiotic (extended or restricted) de-escalation in medical ward Hospital Kuala Lumpur, between Jan 2016 to June 2019. The primary outcome of interest is 30-day all-cause mortality. Kaplan Meier survival curve and Fleming-Harrington test were used to compare the overall survival rates between early, late and those not de-escalated on antibiotic. Multivariable Cox regression was used to determine prognostic factors associated with mortality, and impact of de-escalation (early and late) on 30-day all-cause mortality. All statistical tests were carried out using STATA version 14. A total of 180 patients were included, with 62 deaths (34.4%) and 118 censored events (65.6%). Out of the 62 deaths, 18 deaths (29%) occurred in non-de-escalated group, 28 deaths (45.2%) and 16 deaths (25.8%) in early and late de-escalation group respectively. Fleming-Harrington test showed the overall mortality rates were not significantly different when patient was not de-escalated on extended or restricted antibiotics, compared to those de-escalated early or later (P=0.760). Variables associated with 30-day all-cause mortality were Sequential Organ Function Assessment (SOFA) score on the day of antimicrobial stewardship (AMS) intervention (AHR 6.74, 95% CI 3.98,11.42; P<0.001) , Charlson’s comorbidity score (AHR 2.00, 95% CI 1.56,3.35 ;P=0.009), and the unavailability of C-reactive protein(CRP) trend values were found to be significant factors associated with mortality of patients with infection who were on extended and restricted antibiotic (AHR 3.10, 95% CI 1.56,6.10; P=0.001). After controlling for abovementioned confounders, early and late antibiotic de-escalation were not associated with increased risk of mortality; AHR were 0.58 (95%CI 0.32,1.07; P=0.085) and 0.77 (95%CI 0.38,1.54;P=0.456) respectively. The results of this study reinforces that restricted or extended antibiotic de-escalation in patients does not significantly affect 30-day all-cause mortality compared to continuation with extended and restricted antibiotics. Patient Charlson’s Scoring index, SOFA score and unavailability of CRP trend are significant factors found to be associated with 30-day all-cause mortality.